PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU PKK TENTANG PEMERIKSAAN PAP SMEAR - Shabrina Sari Medina; Ilhami Romus; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBackground: Counseling is one of the approach attempts to improve theknowledge and attitude. This study aimed to know the influence of counselingtoward Family Welfare Movement’s knowledge and attitude about pap smear atTangkerang Timur District of Pekanbaru. Pap smear is one of the method forearly detection of cervical cancer.Materials and Methods: One group pretestpostestanalytic method that using questionnaire was conducted amongst 35persons of Family Welfare Movement at Tangkerang Timur District, Pekanbaru.The measurement of knowledge and attitude conduct 2 times, before and aftercounseling. The counseling perform used presentation method.Results:The resultof knowledge and attitude about Pap Smear when before and after counseling wasthat the knowledge level before counseling on the respondents in high categorywas 20 (57,1%) respondents and low category was 15 (42,9%) respondents. Afterthe counseling, there was incerasing number of respondents whom in highcategory became 26 (72,2%) respondents and decreasing number of respondentsin low category became 9 (25,7%) respondents. Before counseling, respondentswith positive attitude was 22 (62,9%) respondents and negative attitude was 13(37,1%) respondents. After counseling, there was increasing number ofrespondents with positive attitude became 27 (77,1%) respondents anddecreasing number of respondents with negative attitude became 8 (22,9%)respondents. Using Mc.Nemar test, the changes on knowledge and attitude ofFamily Welfare Movement group about pap smear before and after counselingshowed the significancy value was 0,210 for knowledge and for 0,267 attitude.The p-value was 0.05, then the result showed that there was a change inknowledge and attitudes about pap smear before and after counseling, but notsignificant. Multivariate analysis was discontinued because bivariate analysishadp value >0,25.Conclusion: The counseling is influence on improving knowledgeand attitude of Family Welfare Movement RW IX Tangkerang Timur District.Keywords: knowledge, Attitude, counseling, pap smear